2015
DOI: 10.4103/0970-0218.158847
|View full text |Cite
|
Sign up to set email alerts
|

Serological, clinical, and epidemiological profile of human brucellosis in rural India

Abstract: Background:Brucellosis is an important but neglected zoonotic disease in India. Due to frequent animal contact, high prevalence of this disease, though expected in rural population, has not been much studied.Aim:The study was carried out to determine serological, clinical, and epidemiological profile including associated risk factors for human brucellosis in rural India.Materials and Methods:In this cross-sectional study, serum samples from 1,733 individuals residing in rural areas were screened for the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…14,16 While in contrast, no significant sex difference was observed in other studies. 13,24 Furthermore, a female predominance was reported in a small study from Saudi Arabia. 17 These variations are most likely related to the differences in occupation, practice, and habits of individuals among the various study populations.…”
Section: Discussionmentioning
confidence: 97%
“…14,16 While in contrast, no significant sex difference was observed in other studies. 13,24 Furthermore, a female predominance was reported in a small study from Saudi Arabia. 17 These variations are most likely related to the differences in occupation, practice, and habits of individuals among the various study populations.…”
Section: Discussionmentioning
confidence: 97%
“…Goel et al, Mangalgi et al and Yohannes et al noted similar findings. [3][4][5] In the present study, 6 out of 111 patients showed serological evidence of Brucella. 4 out of 6 were males and 2 were females.…”
Section: Discussionmentioning
confidence: 66%
“…[21][22] In South and North Karnataka, 2.14%, 0.92% seropositivity was observed respectively among patients with or without fever and those presenting other symptoms for brucellosis 17 . Mangalgi et al 27 conducted a seroepidemiological survey in three districts of Karnataka viz., Bijapur, Bagalkot, and Gulbarga. They divided into two groups namely, directly exposed and indirectly exposed to animal contacts.…”
Section: Seroprevalence Of Brucellosis Among Febrile Patients (Puo)mentioning
confidence: 99%